Insulin resistance and serum metabolomics improvement in subjects with impaired glucose tolerance treated with Hibiscus esculentus L. - Chen, Lin; Wang, Qi; Sha, Wenjun; Zhang, Cuiping; Shen, Tian; Lu, Ming; Lei, Tao (Vojnosanitetski pregled, 2023)
Background/Aim. Prediabetes (PD) refers to the condition in which the blood sugar level is higher than normal but has not reached the diagnostic criteria for diabetes mellitus (DM) yet. Impaired glucose tolerance (IGT) is a major prediabetic symptom since most patients with type 2 DM have progressed from the previous PD phase. The aim of the study was to observe the changes in serum metabolomics in patients with IGT treated with Hibiscus esculentus L. (H. esculentus) combined with the change of lifestyle. Methods. Sixty patients with IGT were divided into two groups. In one group, the subjects made a lifestyle change (LC group, simple diet control), and the other group of subjects made a lifestyle change combined with H. esculentus (LCH group) treatment with daily consumption of 20 g of dried H. esculentus fruit tea. The aim was to compare the blood glucose, homeostasis model assessment-estimated insulin resistance (HOMA-IR) index, and serum metabolomics after a 60-day clinical observation period. Results. There was no statistical significance in the glucose level between the two groups by the end of the observation period. The HOMA-IR index in the LCH group was lower than in the LC group (1.7 ± 1.1 vs. 2.4 ± 1.2, p = 0.030). Serum metabolomics revealed that the levels of d-galactose, d-glucose, turanose, and uric acid in the LCH group were significantly lower than those in the LC group (16.7 ± 3.9 mmol/L vs. 21.2 ±2.9 mmol/L, 101.5 ± 40.2 mmol/L vs. 132.9 ± 36.7 mmol/L, 1.8 ± 1.6 mmol/L vs. 3.76 ± 2.46 mmol/L, 44.56 ± 15.7 μmol/L vs. 67.8 ± 23.5 μmol /L, respectively). The levels of lactic acid and conjugated linoleic acid in the LCH group were significantly higher than those in the LC group (3.3 ± 0.5 mmol/L vs. 2.3 ± 0.8 mmol/L, 6.9 ± 6.1 mmol/L vs. 2.1 ± 1.2 mmol/L, respectively). Conclusion. H. esculentus, combined with a change of lifestyle, can reduce insulin resistance and the levels of multiple monosaccharides and blood uric acid in IGT patients. Regulation of the metabolism of lactic acid and conjugated linoleic acid may be the potential mechanism of how H. esculentus reduces insulin resistance.